2019
DOI: 10.1126/science.aax6624
|View full text |Cite
|
Sign up to set email alerts
|

MAIT cells are imprinted by the microbiota in early life and promote tissue repair

Abstract: How early-life colonization and subsequent exposure to the microbiota affect long-term tissue immunity remains poorly understood. Here, we show that the development of mucosal-associated invariant T (MAIT) cells relies on a specific temporal window, after which MAIT cell development is permanently impaired. This imprinting depends on early-life exposure to defined microbes that synthesize riboflavin-derived antigens. In adults, cutaneous MAIT cells are a dominant population of interleukin-17A (IL-17A)–producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
430
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(483 citation statements)
references
References 79 publications
(100 reference statements)
23
430
1
1
Order By: Relevance
“…Levels of some cytokines may take up to 3–4 months after delivery to normalize, 33 whereas certain immune cell types appear to normalize within 6 weeks 34 . The importance of early exposure to microbiota for MAIT cell development has been recently shown 35 and may explain some of the variation in MAIT cell frequencies in our study population.…”
Section: Discussionmentioning
confidence: 77%
“…Levels of some cytokines may take up to 3–4 months after delivery to normalize, 33 whereas certain immune cell types appear to normalize within 6 weeks 34 . The importance of early exposure to microbiota for MAIT cell development has been recently shown 35 and may explain some of the variation in MAIT cell frequencies in our study population.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, we recently showed that MAIT cells can respond to a variety of microbiome-related bacteria (Tastan et al, 2018) and that they potentially function to tune or sense the microbial ecosystem throughout mucosal tissues. Two recent papers also show that MAIT cell development and expansion is also directly dependent on the microbiome (Constantinides et al, 2019;Legoux et al, 2019;Oh and Unutmaz, 2019). In one paper, the authors show that CD4-CD8- (double negative, or DN) MAIT cells are a functionally distinct subset that migrate to the skin in mice and are potentially involved in tissue repair (Dias et al, 2018;Constantinides et al, 2019;Oh and Unutmaz, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Two recent papers also show that MAIT cell development and expansion is also directly dependent on the microbiome (Constantinides et al, 2019;Legoux et al, 2019;Oh and Unutmaz, 2019). In one paper, the authors show that CD4-CD8- (double negative, or DN) MAIT cells are a functionally distinct subset that migrate to the skin in mice and are potentially involved in tissue repair (Dias et al, 2018;Constantinides et al, 2019;Oh and Unutmaz, 2019). Thus, it is interesting to note that we observed differences in CD8+ but not in DN MAIT cells in ME/CFS subjects, suggesting that these are different lineages or subsets.…”
Section: Discussionmentioning
confidence: 95%
“…Exhibiting characteristics of both innate and adaptive immunity, innate-like T lymphocytes such as iNKT cells, MAIT cells, and subsets of gd T cells, have emerged as key players in the control of immunity and tissue homeostasis [46][47][48][49] . In striking contrast to Tconv cells, which exit the thymus changes driving progression from one cellular state to the next is lacking.…”
Section: Discussionmentioning
confidence: 99%